Whither the early republic : a forum on the future of the field - Larson, John Lauritz, 1950-; Morrison, Michael A., 1948-2017 (University of Pennsylvania Press, 2005)
Penned by leading historians, the specially-commissioned essays of Whither the Early Republic represent the most stimulating and innovative work being done on imperialism, environmental history, slavery, economic history, politics, and culture in the early Republic.